Cross-cultural adaptation, reliability and validity analysis of the Cantonese-Chinese Manchester Oxford Foot Questionnaire for Foot and Ankle Disorder (Manchester-Oxford Foot Questionnaire HK) - Shu MC Chia; Leung P Ho; Violet Man-Chi Ko; He Xin; Long CB Chow; Patrick Shu-Hang Yung; Samuel Ka-Kin Ling (Journal of Orthopaedics, Trauma and Rehabilitation)
The Manchester–Oxford Foot Questionnaire is a validated English 16-item patient-reported outcome measure for evaluating foot and ankle function. This study aimed to translate a Cantonese Chinese version of the questionnaire and evaluate its validity and reliability among patients with foot and ankle disorders. The translation and cross-cultural adaptation were conducted by forward translation, synthesis of translated versions, backward translation, review, and pre-testing by a panel of healthcare professionals. The test-retest reliability was conducted within 2–4 weeks. Internal consistency and construct validity were evaluated using the Visual Analogue Scale and Short-Form 36. 135 participants were recruited to complete the validation process. The overall reliability coefficient constituted 0.86 (intraclass correlation coefficient = 0.72–0.93). A strong, statistically significant correlation was found between the bodily pain subscale of Short-Form 36 and the pain subscale of the Cantonese Chinese-Manchester-Oxford Foot Questionnaire ( r  = −0.77, p  < 0.001). This was similar to the pain subscale of the Cantonese Chinese-Manchester-Oxford Foot Questionnaire and visual analogue pain score ( r  = 0.77, p  < 0.001). The overall score for the Cantonese Chinese Manchester-Oxford Foot Questionnaire between the healthy control group and the pathological group was statistically different ( p  < 0.001). A good consistency level was found in the questionnaire with a Cronbach's alpha coefficient of 0.78, 0.86, 0.78, 0.85 for pain, walking/standing, social interaction, and the overall domain of the Cantonese Chinese-Manchester-Oxford Foot Questionnaire, respectively. Therefore, this questionnaire can be adapted as a reliable clinical assessment and an outcome measure among the Cantonese Chinese-speaking population.